2015
DOI: 10.1002/jbm.b.33493
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic microstructural reorganization during suture retention strength evaluation of electrospun vascular scaffolds

Abstract: Suture retention strength (SRS) is commonly used as a measure the ability of sutures to adhere implants to surrounding tissue. While SRS is widely employed, surprisingly its effects on graft microstructure have not been characterized. This is particularly germane to the broad utilization of electrospun implants in tissue engineering. These implants need to retain their initial nanoscale topography while simultaneously preserving clinically critical mechanical properties. We examined the suture-driven microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Above 300 m/min, mechanical deformation was observed on the fibers because of the high mechanical stress and affected the fiber orientation in a negative way [45]. In a study by Chaparro et al [46], randomly distributed PCL fibers were spun onto a 53 mm diameter steel rod rotated at 9000 r/min (net peripheral speed of 84.6 m/min), while aligned PCL fibers were spun onto a rotating Yalcin Enis and Gok Sadikoglu mandrel having a 2.01 m circumference (diameter: 640 mm), rotated at 500 r/min (providing a peripheral speed of 2000 m/min) [46].…”
Section: Yalcin Enis and Gok Sadikoglumentioning
confidence: 96%
See 1 more Smart Citation
“…Above 300 m/min, mechanical deformation was observed on the fibers because of the high mechanical stress and affected the fiber orientation in a negative way [45]. In a study by Chaparro et al [46], randomly distributed PCL fibers were spun onto a 53 mm diameter steel rod rotated at 9000 r/min (net peripheral speed of 84.6 m/min), while aligned PCL fibers were spun onto a rotating Yalcin Enis and Gok Sadikoglu mandrel having a 2.01 m circumference (diameter: 640 mm), rotated at 500 r/min (providing a peripheral speed of 2000 m/min) [46].…”
Section: Yalcin Enis and Gok Sadikoglumentioning
confidence: 96%
“…Therefore, most of the studies use large diameter collectors (630 mm [42], 102 mm [44], 32 mm [45], and 640 mm [46]) for accessible rotational speeds. Matsuda et al [43] reported that they achieved partial fiber orientation at 32.02 m/min for a 3 mm rotating mandrel diameter [43] which had been explained by Edwards et al as having an insufficient peripheral velocity [45].…”
Section: Yalcin Enis and Gok Sadikoglumentioning
confidence: 99%
“…Often referred to as the tissue-engineering “triad,” this foundational concept of cells, scaffolds, and signals has informed strategies for numerous outcomes, such as bone regeneration following complex fractures or the development of vasculature in vitro to replace diseased vessels (3, 4). Significant advances in the field have resulted from this paradigm.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Suture retention (SR) testing (n = 10) was performed using the same TestResources TM frame with 0.75 cm × 4 cm rectangular strips cut from the electrospun templates (along the same direction and orientation as the dogbone punches), following the "straight-across" method with a "v-shape" failure mode, consistent with SR testing methods outlined in the American National Standard ANSI/AAMI VP20:1994 entitled "Cardiovascular Implants -Vascular Graft Prostheses" [16]. Briefly, the SD templates fabricated from all three deposition plates were tested using an Ethicon 6-0 (0.7 metric) PDS II (polydioxanone) suture fed through one end of the rectangular strip (3 mm from the center of the edge).…”
Section: Suture Retention Testingmentioning
confidence: 99%
“…The "V" shaped failure mode indicates a successful failure during SR testing [16]. LD templates, however, were in fact too strong for the Ethicon sutures.…”
Section: Suture Retention Testingmentioning
confidence: 99%